Pancytopenia in pregnancy: a case series - Sangamesh Mathapati; Aruna Biradar; Laxmi Sangolli; Gamini BS; Sridevi HS (Barpeta Obstetrics and Gynaecological Society, 2021)
Pregnancy is a state of high metabolic demand. Anaemia and thrombocytopenia are common during pregnancy, which is the result of normal dilutional effect of increased plasma volume seen during pregnancy. These are frequently seen in pregnant women but are not severe enough to require interventions unless aggravated by deficiency of micronutrients. Anaemia due to nutritional deficiency is common in developing countries.